The Online English Extensive Reading Activities Using Google Classroom in Pandemic Covid-19 - Euis Meinawati; Prapti Wigati Purwaningrum; Herlin Widasiwi Setianingrum; Sufi Alawiyah; Chodidjah Chodidjah (Makassar State University, 2021)
Abstract. The study purpose was to increase English extensive reading activities using google classroom in online learning process, especially in pandemic Covid-19 situation. This research is action research which used exploratory mixed method using Elliot model. Process of collecting data used observation, interview, diary note, and test. The technique of analysis data was reduction, presentation, and taking conclusion. The research finding show that google classroom has given significant impact on English extensive reading in the classroom. Some students think that it is easy to delivery assignment and correction of the task. They can do it out of class. It can be seen from the average score from reading test in pretest is 53 and posttest is 87. Therefore, integrating digital literacy with the reading learning is a big challenge for the learning and teaching process. Keywords: Extensive Reading, Google Classroom, Online Class, Covid-19